Hit-and-Run Epigenetic Editing for Vectors of Snail-Borne Parasitic Diseases - Luviano, Nelia; Duval, David; Ittiprasert, Wannaporn; Allienne, Jean-Francois; Tavernier, Geneviève; Chaparro, Cristian; Cosseau, Celine; Grunau, Christoph (Frontiers in Cell and Developmental Biology, 2022)
Snail-borne parasitic diseases represent an important challenge to human and animal health. Control strategies that target the intermediate snail host has proved very effective. Epigenetic mechanisms are involved in developmental processes and therefore play a fundamental role in developmental variation. DNA methylation is an important epigenetic information carrier in eukaryotes that plays a major role in the control of chromatin structure. Epigenome editing tools have been instrumental to demonstrate functional importance of this mark for gene expression in vertebrates. In invertebrates, such tools are missing, and the role of DNA methylation remains unknown. Here we demonstrate that methylome engineering can be used to modify in vivo the CpG methylation level of a target gene in the freshwater snail Biomphalaria glabrata, intermediate host of the human parasite Schistosoma mansoni. We used a dCas9-SunTag-DNMT3A complex and synthetic sgRNA to transfect B. glabrata embryos and observed an increase of CpG methylation at the target site in 50% of the hatching snails.